Faktor - Faktor Yang Mempengaruhi Belanja Daerah Kabupaten Kota Di Provinsi Jawa Barat - Amylia, Fifi; Ulinnuha, Ahmad; Khif Dhiah, Nafisatul; Mutiara Azkia, Anjani; Anwar, Saiful (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2022)
This research aims to analyze region's native income (pad), results-sharing funds (DBH), and population (jp) of regional spending (db) districts (west Java). The population of this research is eight counties. The sample used in this study is the use of the random sampling method. The data analysis technique by using the regression analysis of the panel. Based on analysis already done, it may be concluded that partial original-income (pad) and outsource funds (DBH) have a negative and insignificant impact on area spending, while the number of people (jp) has a positive and significant impact on local spending. Simultaneously, DBH, jp has a significant impact on regional spending. The study provides implications specifically to the county/provincial governments of west Java to increase quality and resources such as natural resources and human resources that are expected to boost local reception and cut down on the central government's transfer fund.